Cordycepin-loaded protein-polysaccharide ternary composite nanoparticles as well as preparation method and application thereof
By using sodium alginate and chitosan on the zein nanoparticles to form the ternary composite nanoparticles of Cordycepsin loading, the problems of high toxicity and short action time of Cordycepsin preparations were solved, and higher biosafety and anti-inflammatory effects were achieved.
Patent Information
- Application Number
- CN202411901436.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-23
AI Technical Summary
The existing Cordyceps preparations have limited their clinical use due to their high toxicity and short action time.
The anti-solvent method combined with layer-level electrostatic stacking method was used to modify the zein nanoparticles using sodium alginate and chitosan to form the ternary composite nanoparticles loaded with Cordycepsin.
It improves the biosafety and embedding rate of Cordycepsin, extends the drug's action time, significantly reduces toxicity, and has certain anti-inflammatory effects.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of cordycepin nano drug delivery system, and in particular to a protein-polysaccharide ternary nanoparticle loaded with cordycepin by double-modifying zein with sodium alginate and chitosan, and a preparation method and application thereof. Background Art
[0002] Cordycepin (3′-deoxyadenosine) is a derivative of the nucleoside adenosine and is the main component of Cordyceps sinensis. Studies have shown that cordycepin has anti-inflammatory, immunomodulatory, anti-diabetic, anti-hyperlipidemia, antioxidant effects, as well as cardiovascular disease prevention and anti-cancer effects. Currently, the research on cordycepin is becoming an extremely active field in the fields of pharmaceutical chemistry, anti-aging, beauty, and health care products. However, cordycepin is rapidly deaminated by adenosine deaminase (ADA) in the body and becomes 3'-deoxyinosine nucleoside with minimal biological activity (Li Jing, Jiang Hanying. Metabolic characteristics and pharmacological effects of cordycepin in vivo [J]. Foreign Medicine (Traditional Chinese Medicine), 2005, (05): 283-285+293.), which limits its clinical use.
[0003] Nanoparticles are a common type of nano-scale delivery system, usually with high molecular polymers as wall materials, which can effectively encapsulate and carry natural active ingredients. Proteins and polysaccharides are two major types of biopolymers. They have the advantages of wide sources, safety and non-toxicity, good biocompatibility, and easy preparation into nanomaterials. They are widely used to construct nano-scale carriers for the preservation and delivery of bioactive substances. For example, Chinese patent CN107281109A uses O-carboxymethyl chitosan as a cordycepin nano drug carrier, adopts an ionic crosslinking method, and uses sodium tripolyphosphate as a crosslinking agent to prepare cordycepin / O-carboxymethyl chitosan nanoparticles. Chinese patent CN116172974A uses EDC and NHS to activate the carboxyl groups of polyethylene glycol and polyethylene glycol-biotin to obtain NHS-polyethylene glycol and NHS-polyethylene glycol-biotin intermediates, and the intermediates are covalently bonded to the amino group of cordycepin to obtain cordycepin-polyethylene glycol and cordycepin-polyethylene glycol-biotin, and cordycepin nanoparticles are obtained by self-assembly. The above technical solutions all have the problems of low encapsulation efficiency and complicated preparation methods. Therefore, it is urgent to develop a cordycepin preparation with long drug action time, high bioavailability and suitable for clinical use. Summary of the invention
[0004] In view of the problems raised in the background technology, the present invention aims to provide a protein-polysaccharide ternary composite nanoparticle loaded with cordycepin and a preparation method and application thereof. The present invention adopts an anti-solvent method combined with a layer-by-layer electrostatic stacking method, and uses sodium alginate and chitosan as raw materials to attach to the surface of zein nanoparticles to prepare ternary composite nanoparticles, so as to improve the stability of zein nanoparticles and the encapsulation rate of cordycepin.
[0005] In a first aspect, the present invention provides a protein-polysaccharide ternary composite nanoparticle loaded with cordycepin, with zein encapsulating cordycepin as the core and sodium alginate and chitosan assembled into the shell, to construct a composite nanoparticle with a core-shell structure for delivering cordycepin.
[0006] The particle size of the nanoparticles is about 200nm and the potential is 40-50mV.
[0007] In a second aspect, the present invention provides a method for preparing the above-mentioned protein-polysaccharide ternary composite nanoparticles loaded with cordycepin, which specifically comprises the following steps: (1) Preparation of an ethanol solution of cordycepin-zein: dissolving zein in an ethanol aqueous solution, adding cordycepin, and stirring to dissolve, thereby obtaining an ethanol solution of cordycepin-zein; wherein the concentration of zein in the ethanol solution of cordycepin-zein is 20 mg / mL, and the mass ratio of cordycepin to zein is 0.025-0.1:1. The volume fraction of ethanol in the ethanol aqueous solution is 80%.
[0008] (2) Preparation of a dispersion of sodium alginate-modified zein nanoparticles loaded with cordycepin: slowly dropwise adding the cordycepin-zein ethanol solution obtained in step (1) into the sodium alginate solution, and stirring to obtain a dispersion at a stirring speed of 400-800 rpm for 30-60 min; wherein the concentration of the sodium alginate solution is 1-2 mg / mL, and the solvent is water; and the volume ratio of the ethanol aqueous solution of cordycepin-zein to the sodium alginate solution is 1:4; (3) Preparation of cordycepin-loaded sodium alginate-chitosan dual-modified zein nanoparticle dispersion: The cordycepin-loaded sodium alginate-chitosan dual-modified zein nanoparticle dispersion obtained in (2) was slowly added dropwise to the chitosan solution at a stirring speed of 400-800 rpm for 30-60 min. Then, the organic solvent was removed under reduced pressure on a rotary evaporator and the volume was made up to 20 mL with deionized water to obtain cordycepin-loaded sodium alginate-chitosan dual-modified zein nanoparticle dispersion.
[0009] The concentration of the chitosan solution is 0.1-2 mg / mL, and the solvent is an acetic acid solution with a volume concentration of 1%.
[0010] The volume ratio of the sodium alginate-modified zein nanoparticle dispersion loaded with cordycepin to the chitosan solution is 1:1.
[0011] (4) freeze-drying the sodium alginate-chitosan dual-modified zein nanoparticle dispersion loaded with cordycepin obtained in step (3) to obtain protein-polysaccharide ternary composite nanoparticles loaded with cordycepin.
[0012] In a third aspect, the present invention provides the use of the above-mentioned protein-polysaccharide ternary composite nanoparticles loaded with cordycepin in the preparation of anti-inflammatory drugs.
[0013] The inflammation described in the present invention is osteoarthritis.
[0014] In a fourth aspect, the present invention also provides a pharmaceutical composition comprising the above-mentioned protein-polysaccharide ternary composite nanoparticles loaded with cordycepin.
[0015] In one embodiment, the anti-inflammatory application is to inhibit the expression of inflammatory factors in osteoarthritis.
[0016] Compared with the prior art, this application has the following beneficial effects: This application uses cordycepin as the active ingredient of the drug. The toxicity and action time of the cordycepin factor itself limit its use. This application adopts an anti-solvent method combined with a layer-by-layer electrostatic accumulation method to prepare protein-polysaccharide composite nanoparticles loaded with cordycepin, which reduces the toxicity of cordycepin and has good biosafety. At the same time, the protein-polysaccharide composite nanoparticles loaded with cordycepin have a sustained release effect and can increase the action time of the drug. The protein-polysaccharide composite nanoparticles loaded with cordycepin have a certain anti-inflammatory effect as verified by an in vitro model. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0018] Figure 1 This is a flow chart of the cordycepin-loaded calcium alginate-chitosan microspheres prepared in Example 1.
[0019] Figure 2 This is a microscope image of the cordycepin-loaded calcium alginate-chitosan microspheres prepared in Example 1.
[0020] Figure 3 This is a diagram of the high performance liquid chromatography detection method for cordycepin.
[0021] Figure 4 This is a graph showing the effect of different pH values on the particle size of protein-polysaccharide composite nanoparticles loaded with cordycepin.
[0022] Figure 5 This is a diagram of the encapsulation efficiency of different dosages of protein-polysaccharide composite nanoparticles loaded with cordycepin.
[0023] Figure 6 This is the release curve of protein-polysaccharide composite nanoparticles loaded with cordycepin, where the abscissa represents time and the ordinate represents the drug release ratio.
[0024] Figure 7 Infrared spectra of raw materials, synthetic samples and mixtures of samples and raw materials for preparing nanoparticles.
[0025] Figure 8 The graph shows the changes in average particle size, PDI and potential of cordycepin-loaded protein-polysaccharide composite nanoparticles under low-temperature storage conditions.
[0026] Fig. 9 The effects of free cordycepin and cordycepin-loaded protein-polysaccharide composite nanoparticles with different concentrations on the activity of L929 cells.
[0027] Fig.10 is the expression level of TNF-α and IL-6 in each group in the rat osteoarthritis model. DETAILED DESCRIPTION
[0028] The present application is further described in detail below in conjunction with specific embodiments. The present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present application more thoroughly understood and comprehensive. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present application. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application.
[0029] Cordycepin (3′-deoxyadenosine) is a derivative of the nucleoside adenosine and is the main component of Cordyceps sinensis. Studies have shown that cordycepin has anti-inflammatory, immunomodulatory, anti-diabetic, anti-hyperlipidemia, antioxidant effects, as well as cardiovascular disease prevention and anti-cancer effects. In order to further develop the application potential of cordycepin, this application adopts an anti-solvent method combined with a layer-by-layer electrostatic stacking method to prepare protein-polysaccharide ternary composite nanoparticles loaded with cordycepin, and cell experiments have confirmed that it can reduce the toxicity of cordycepin. The in vitro model verifies that the protein-polysaccharide composite nanoparticles loaded with cordycepin have a certain anti-inflammatory effect.
[0030] The following is further described in conjunction with specific embodiments. The raw materials involved in the following specific embodiments, unless otherwise specified, can all be commercially available; the instruments used, unless otherwise specified, can all be commercially available; the processes involved, unless otherwise specified, are all routinely selected by those skilled in the art. Example 1
[0031] This embodiment provides a method for preparing cordycepin-loaded calcium alginate / chitosan microspheres by a double emulsion cross-linking method, which specifically comprises the following steps: (1) Prepare the oil phase: Add 6% Span-80 to liquid paraffin and stir magnetically for 30 min to completely emulsify it (prepare 2 portions).
[0032] (2) Prepare a 1.5% (w / v) sodium alginate solution, add cordycepin to the sodium alginate solution, and stir to completely dissolve it.
[0033] (3) Prepare 7% (w / v) calcium chloride solution to be used as a cross-linking agent.
[0034] (4) Under mechanical stirring, sodium alginate solution and calcium chloride solution containing cordycepin were added dropwise to the oil phase using a syringe, and the oil-water ratio was set to 3:2. Stirring was maintained at a constant speed for more than 30 min to form emulsions.
[0035] (5) The two prepared emulsions were mixed, the crosslinking temperature was maintained, the stirring speed was 800 rpm, and the curing was carried out for 4 h.
[0036] (6) After cross-linking and curing, the microspheres were centrifuged, washed three times with anhydrous ethanol, and washed twice with aqueous solution to obtain calcium alginate microspheres loaded with cordycepin.
[0037] (7) A 0.1% chitosan solution was prepared using a 10% acetic acid solution, and the obtained calcium alginate microspheres were immersed in the chitosan solution for 5-10 min. The calcium alginate-chitosan microspheres loaded with cordycepin were obtained by centrifugation and the supernatant was discarded.
[0038] 1. Through the above method process (such as Figure 1 ) prepared calcium alginate / chitosan microspheres loaded with cordycepin, and observed their morphology under a microscope. Figure 2 (a) Calcium alginate microspheres loaded with cordycepin. Figure 2 (b) Calcium alginate-chitosan microspheres loaded with cordycepin. Microscopic observation shows that the microspheres are spherical and relatively dispersed, but their size uniformity is not high.
[0039] 2. Detection of cordycepin content by high performance liquid chromatography. The specific steps are as follows: Determination of detection wavelength: For the determination wavelength of cordycepin, the literature generally reports that it is between 250-260 nm. In this experiment, we scanned the cordycepin standard solution in the wavelength range of 200-500 nm with a UV spectrophotometer, measured the wavelength with the most significant cordycepin absorption peak and the greatest sensitivity, and set the detector to detect at this wavelength. Determination of mobile phase: In literature reports, phosphate buffer is mostly used as the mobile phase for the analysis of cordycepin and adenosine. This experiment tested mobile phase conditions such as water-methanol-acetic acid solution (185:14:1), methanol-10 mM potassium dihydrogen phosphate solution (15:85), acetonitrile aqueous solution, and methanol aqueous solution. The cordycepin standard was scanned at a wavelength of 200-500 nm by UV spectrophotometer. Figure 3 As shown in (a), the absorption peak of cordycepin at 260 nm is the most significant and has the highest sensitivity, so the detector is set to detect at 260 nm. The acetonitrile aqueous solution was finally selected as the mobile phase for the high-performance liquid chromatography determination of cordycepin. Its composition is simple and has little effect on the chromatographic column. By determining different samples and adjusting the mobile phase ratio, the final ratio of 10+90=acetonitrile+water solution was finally established as the mobile phase. The HPLC chromatogram of the cordycepin standard solution is shown in Figure 3 (c). The final chromatographic conditions were as follows: chromatographic column: C18 column, 250 mm long, 4.6 mm inner diameter, 5 µm particle size; temperature: 35°C; mobile phase: acetonitrile + water = 10 + 90; flow rate: 1.0 mL / min; detection wavelength: 260 nm; injection volume: 10 μL. The standard curve was drawn with the concentration of the standard cordycepin solution as the horizontal axis and the peak area as the vertical axis. Figure 3 (b) The standard curve equation is y=21.10657x+2.37645, and the correlation coefficient is R 2 It is 0.9999.
[0040] 3. The cumulative drug release rate of cordycepin-loaded calcium alginate-chitosan microspheres is as follows: Take 10 mg of calcium alginate-chitosan microspheres containing cordycepin, dissolve them in 1 mL of water, and put them into a dialysis bag after dissolution. Add 15 mL of freshly prepared PBS to the centrifuge tube as the release medium to simulate the in vivo environment; place the centrifuge tube on a shaker at 37℃±0.5℃ and 100 r / min for in vitro drug release experiments; take out a certain volume of release medium from the centrifuge tube at the specified time point, and immediately replenish the same volume of freshly prepared PBS solution after each removal. Filter the removed release medium through a 0.22 μm disposable syringe filter, and detect the drug concentration on the machine according to the high-performance liquid chromatography method, and calculate the cumulative release rate at each specified time point.
[0041] The microspheres loaded with cordycepin were slowly released in a PBS solution simulating the in vivo environment. The slow-release medium did not contain cordycepin according to the HPLC analysis. The reason may be that the slow-release medium was used too much, resulting in too low a concentration, or the drug loading was too low. Therefore, the free cordycepin in the preparation process was measured, and the results showed that the free cordycepin was almost consistent with the dosage, proving that this preparation method failed to successfully encapsulate the cordycepin and failed to achieve a slow-release effect. Example 2
[0042] This example provides a method for preparing protein-polysaccharide composite nanoparticles loaded with cordycepin, and compares the effect of the pH of the sodium alginate solution on the nanoparticles. The method specifically comprises the following steps: (1) Dissolve 0.2 g of zein in 10 mL of 80% ethanol-water solution, then add 20 mg of cordycepin and stir thoroughly to dissolve it to obtain a cordycepin-zein ethanol-water solution.
[0043] (2) Preparation of sodium alginate solution: Dissolve 4 mg of sodium alginate in 20 mL of deionized water and stir overnight to fully dissolve. Adjust the pH value to 3, 4, 5, 6, or 7.
[0044] (3) Preparation of cordycepin-loaded sodium alginate-modified zein nanoparticle dispersion: Take 2 mL of the cordycepin-zein ethanol solution obtained in step (1), slowly add it dropwise to 8 mL of the sodium alginate solution obtained in step (2), and stir for 60 min.
[0045] (4) Preparation of chitosan solution: Dissolve 2 mg of chitosan in 10 mL of 1% acetic acid solution and stir overnight to allow it to fully dissolve.
[0046] (5) Preparation of cordycepin-loaded sodium alginate-chitosan dual-modified zein nanoparticle dispersion: The cordycepin-loaded sodium alginate-chitosan dual-modified zein nanoparticle dispersion obtained in (3) was slowly added dropwise to the chitosan solution obtained in (4) and stirred for 60 min; then, the organic solvent was removed under reduced pressure on a rotary evaporator and the volume was made up to 20 mL with deionized water to obtain a cordycepin-loaded sodium alginate-chitosan dual-modified zein nanoparticle dispersion.
[0047] The average particle size, polydispersity index (PDI) and zeta potential of the nanoparticles were measured using a Malvern laser particle size analyzer.
[0048] The average particle size and polydispersity index (PDI) of each nanoparticle during the preparation of nanoparticles loaded with cordycepin are shown in Figure 2. Figure 4As shown, different pH values of sodium alginate will affect the prepared nanoparticles, and the particle size result is best when the pH is 4. As the pH increases, the particle size will also increase. Finally, it was selected to prepare nanoparticles under slightly acidic conditions. Example 3
[0049] This embodiment provides a method for preparing a sodium alginate-modified cordycepin-loaded zein nanoparticle dispersion, wherein the pH of the sodium alginate solution is 4, and the amount of sodium alginate is adjusted to 20 mg, 10 mg, 4 mg, 2 mg, and 0 mg. The remaining preparation steps and the addition amount of each component are the same as in Example 2. The average particle size, polydispersity index (PDI) and zeta potential of the above-mentioned nanoparticles were measured using a Malvern laser particle size analyzer. Table 1 shows the effect of different sodium alginate concentrations on the average particle size, PDI and ζ-potential of cordycepin zein nanoparticles. It can be seen that as the sodium alginate concentration continues to increase, the particle size and PDI of the cordycepin zein nanoparticles modified with sodium alginate continue to increase. When the sodium alginate concentration is 0.02%, its particle size is the smallest, the dispersibility is also good, and the potential is generally negative.
[0050] Table 1 Average particle size, PDI and ζ-potential of cordycepin zein particles coated with different concentrations of alginate Example 4
[0051] This example investigates the effects of different chitosan dosages and different sodium alginate-coated cordycepin nanoparticles on average particle size, polydispersity index (PDI) and zeta potential. The results are shown in Tables 2-4.
[0052] Table 2 Average particle size (nm)
[0053] Table 3 Polydispersity Index (PDI)
[0054] Table 4 Zeta potential (MV)
[0055] Table 2-4 shows the average particle size, PDI and ζ-potential of cordycepin zein nanoparticles coated with sodium alginate modified by chitosan at different concentrations. When chitosan is used for coating, floccules will be produced when its concentration is too high (the table uses "--" to indicate). When chitosan of different concentrations is used to coat sodium alginate of different concentrations, when the chitosan concentration is 0.02%, the sodium alginate concentration is 0.01% and 0.02%, all of which have good particle size and PDI, and their potential will also be positive. After comprehensive comparison, the protein-polysaccharide composite nanoparticles loaded with cordycepin with a sodium alginate concentration of 0.02% and a chitosan concentration of 0.02% were selected as the object of subsequent research. Example 5
[0056] Based on the optimal sodium alginate solution and chitosan solution determined in the previous example, that is, the amount of sodium alginate is 4 mg, the pH is 4; the amount of chitosan is 2 mg, and the amount of cordycepin added is adjusted to 20 mg, 10 mg, and 5 mg. The remaining preparation steps and the amount of each component added are the same as in Example 2.
[0057] The protein-polysaccharide composite nanoparticles loaded with cordycepin of the present invention are weighed and then re-dissolved after freeze-dried samples are centrifuged at 10,000 rpm for 40 minutes to obtain the supernatant, and the absorbance is measured at 260 nm using an ultraviolet spectrophotometer. The encapsulation efficiency and drug loading are calculated as follows: Encapsulation rate (%) = (total cordycepin content (mg) - free cordycepin content (mg)) / total cordycepin content (mg) * 100 Drug loading (%) = (total cordycepin content (mg) - free cordycepin content (mg)) / total weight of nanoparticles (mg) * 100 The drug release curve of cordycepin-loaded protein-polysaccharide composite nanoparticles was determined by dialysis method.
[0058] The encapsulation efficiency, drug loading and drug release results of protein-polysaccharide composite nanoparticles loaded with cordycepin are shown in Figure 2. Figure 5 As shown, ZCSC with different concentrations of cordycepin has different encapsulation rates. When the concentration of cordycepin is 2 mg / mL, the encapsulation effect of ZCSC is the best, with an encapsulation rate of 78.6%. Using 2 mg / mL of cordycepin, ZCSC NPs were prepared according to the above-mentioned optimal sodium alginate concentration and chitosan concentration, and the drug loading capacity was 6.4%. In summary, the use of 2 mg / mL of cordycepin, 0.02% sodium alginate and 0.02% chitosan to prepare ZCSC has the best results, with a particle size of 195.53 nm, a PDI of 0.195, a zeta potential of 49.3 mV, an encapsulation rate of 78.6%, and a drug loading capacity of 6.4%. This result was used for the next step of research. Its drug release curve is shown in Figure 6 As shown in the figure, the drug release curve shows that ZCSC can release about 40% slowly within 2 hours, and can release about 70% cumulatively after 34 hours, and the release curve is stable.
[0059] Infrared spectroscopy was used to analyze cordycepin, zein, sodium alginate, chitosan, sodium alginate-modified zein nanoparticles loaded with cordycepin, and sodium alginate-chitosan double-modified zein nanoparticles loaded with cordycepin. The FT-IR spectra of zein (zein), cordycepin (Cor), sodium alginate (SA), and chitosan (CS) are shown in Figure 1. Figure 7 As shown in (a), the spectra of zein-loaded nanoparticles (ZC), sodium alginate-modified zein-loaded nanoparticles (ZCSA), cordycepin-loaded protein-polysaccharide composite nanoparticles (ZCSC), and mixtures of various raw materials (Mixtures) are shown in Figure 7 As shown in (b), by comparing the characteristic peaks of different samples, it can be concluded that cordycepin is encapsulated in zein nanoparticles, and sodium alginate and chitosan modify the nanoparticles.
[0060] The protein-polysaccharide composite nanoparticle dispersion loaded with cordycepin was placed in a 4°C refrigerator, and the average particle size, polydispersity index (PDI) and zeta potential were measured at 1d, 3d, 5d and 7d. The results showed that under the low-temperature storage condition for one week, the average hydrated particle size, PDI and potential of the sample ZCSC had basically no significant changes. Figure 8 , indicating that it has good stability under low temperature conditions. Example 6
[0061] The cordycepin-loaded protein-polysaccharide composite nanoparticles (ZCSC) prepared by the best preparation method optimized in the above example (2 mg / mL cordycepin, 0.02% sodium alginate at pH 4, and 0.02% chitosan) were used for cell and animal experiments.
[0062] The cytotoxicity evaluation of protein-polysaccharide composite nanoparticles loaded with cordycepin specifically includes the following steps: 1. Cytotoxicity assay: The in vitro toxicity of cordycepin and protein-polysaccharide composite nanoparticles loaded with cordycepin on L929 cells was tested using the MTT method. First, L929 cells in the logarithmic growth phase were selected, inoculated in a 96-well plate at a density of 8,000 cells per well, and cultured in a carbon dioxide incubator for 12 hours. Subsequently, cordycepin and protein-polysaccharide composite nanoparticles loaded with cordycepin at different concentrations (calculated according to the amount of cordycepin loaded in the nanoparticles) were prepared, and they were diluted to the required concentrations with blank DMEM culture medium. The original culture medium in the well was discarded, and the culture medium containing samples of different concentrations was added and cultured for 24 hours. After that, 20 μL of MTT solution was added to each well, incubated for another 4 hours, all the liquid in the well was discarded, 150 μL of DMSO was added, and incubated in a shaker in the dark for 15 minutes, and the absorbance at 570 nm was measured using an enzyme reader.
[0063] 3. Results The MTT assay was used to study the cell viability of L929 cells co-incubated with cordycepin and cordycepin-loaded protein-polysaccharide composite nanoparticles for 24 h. Fig. 9 As shown in the figure. It can be seen from the figure that when the concentration of cordycepin is 0.1 mg / mL, the cell survival rates of cordycepin and protein-polysaccharide composite nanoparticles loaded with cordycepin are both higher than 80%, but as the concentration of cordycepin increases, the survival rate of L929 cells gradually decreases. The cell survival rate of protein-polysaccharide composite nanoparticles loaded with cordycepin always remains at a high level. By comparing with free cordycepin, it can be seen that the protein-polysaccharide composite nanoparticles loaded with cordycepin have less toxicity and have a certain cell proliferation effect. Example 7
[0064] Evaluation of the anti-inflammatory effect of cordycepin-loaded protein-polysaccharide composite nanoparticles in osteoarthritis specifically includes the following steps: 1. Establishment of rat osteoarthritis model and drug administration SD male rats weighing about 200 g were anesthetized with 1 mL of 7% chloral hydrate. A parapatellar incision was made on the medial side of the rat's knee joint, the skin was separated, the knee capsule was opened, the fat was peeled off, the meniscus tibial ligament of the medial meniscus was exposed, the medial meniscus tibial ligament was cut with a scalpel blade to make the joint unstable, and the wound was sutured with sutures. The sham group (Sham) only exposed the ligament without cutting it. After 4 weeks of modeling, nanoparticles loaded with cordycepin were injected into the rat's bone joint cavity once every two weeks. After 4 weeks of administration, the rats were killed and blood was taken for analysis of their inflammatory factors.
[0065] ELISA kits were used to detect the expression of TNF-α and IL-6. The results showed that osteoarthritis was induced in rats by cutting off one side of the meniscus, and the rats were treated by intra-articular administration. After 4 weeks of treatment, the rats were killed and blood was taken for ELISA experiments. The results were as follows Fig.10 As shown in the figure, the Sham group represents the sham operation group, the PBS group represents the osteoarthritis group, the ZCSA group represents the protein-polysaccharide composite nanoparticles without cordycepin loading, the ZCSC group represents the protein-polysaccharide composite nanoparticles loaded with cordycepin, and the Free Cor group represents the free cordycepin group. The results showed that compared with the PBS group, the ZCSA group, and the Free Cor group, the expression levels of inflammatory factors TNF-α and IL-6 in the ZCSC group were significantly reduced, indicating that the protein-polysaccharide composite nanoparticles loaded with cordycepin have a certain anti-inflammatory effect.
[0066] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0067] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent application shall be subject to the attached claims, and the description may be used to interpret the content of the claims.
Claims
1. A protein-polysaccharide ternary composite nanoparticle loaded with cordycepin, characterized in that: Cordycepin-encapsulated zein was used as the core, and sodium alginate and chitosan were assembled into the shell to construct composite nanoparticles with a core-shell structure for delivering cordycepin.
2. The protein-polysaccharide ternary composite nanoparticles loaded with cordycepin according to claim 1, characterized in that: The particle size of the composite nanoparticles is 190-210 nm; the potential is 40-50 mV.
3. The method for preparing the protein-polysaccharide ternary composite nanoparticles loaded with cordycepin according to claim 1 or 2, characterized in that: The specific steps include: (1) dissolving zein in an ethanol aqueous solution, adding cordycepin, and stirring thoroughly to dissolve, thereby obtaining solution A; (2) Add solution A dropwise into the sodium alginate solution and stir to obtain dispersion B. (3) Slowly drop dispersion B into the chitosan solution at a stirring speed of 400-800 rpm for 30-60 min; remove the organic solvent by vacuum rotary evaporation and dilute with water to obtain dispersion C; (4) The dispersion C is freeze-dried to obtain protein-polysaccharide ternary composite nanoparticles loaded with cordycepin.
4. The method for preparing cordycepin-loaded protein-polysaccharide ternary composite nanoparticles according to claim 3, characterized in that: In the solution A described in step (1), the concentration of zein is 20 mg / mL, and the mass ratio of cordycepin to zein is 0.025-0.1:
1.
5. The method for preparing cordycepin-loaded protein-polysaccharide ternary composite nanoparticles according to claim 3, characterized in that: The concentration of the sodium alginate solution in step (2) is 1-2 mg / mL, and the pH is 3-5.
6. The method for preparing cordycepin-loaded protein-polysaccharide ternary composite nanoparticles according to claim 3, characterized in that: The volume ratio of solution A to sodium alginate solution in step (2) is 1:
4.
7. The method for preparing cordycepin-loaded protein-polysaccharide ternary composite nanoparticles according to claim 3, characterized in that: The concentration of the chitosan solution in step (3) is 0.1-2 mg / mL, and the solvent is 1% acetic acid solution.
8. The method for preparing cordycepin-loaded protein-polysaccharide ternary composite nanoparticles according to claim 3, characterized in that: The volume ratio of the dispersion B to the chitosan solution is 1:
1.
9. Use of the cordycepin-loaded protein-polysaccharide ternary composite nanoparticles according to claim 1 or 2 in the preparation of anti-inflammatory drugs.
10. A pharmaceutical composition, characterized in that The protein-polysaccharide ternary composite nanoparticles containing cordycepin according to claim 1 or 2.
Citation Information
Patent Citations
Cordycepin / O-carboxymethyl chitosan nanoparticle and preparation method thereof
CN107281109A
Cordycepin nanoparticles as well as preparation method and application thereof
CN116172974A
Cordycepin nanometer sustained-release capsule and preparation method thereof
CN103976981A
Quercetin-loaded protein-polysaccharide ternary composite nanoparticles as well as preparation method and application thereof
CN118045062A